Strategi Pemasaran Program Wakaf Yayasan Hutan Wakaf Bogor - Ismail Fakhri; Irfan Syauqi Beik; Endar Hasafah Nugrahani (AL-MUZARA'AH, 2023)
The high rate of deforestation makes the forest waqf program attractive to be developed as a support for the reforestation program. The research will identify variables that can influence waqf decision-making. Data collection used a research questionnaire with a sample of 100 people using Judgment Sampling. The analytical tool used in this research is Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results showed that registered buyers of forest waqf products at the Bogor Waqf Forest Foundation were dominated by millennials with single status and incomes between IDR 1,000,000 – IDR 2,000,000. Brand and customer trust affect the marketing effectiveness of trust in forest waqf products. The priorities for the marketing strategy for forest waqf products include strengthening brand image, increasing consumer confidence, conducting social activities, maintaining communication with consumers, and conducting regular data analysis and evaluation.